The goalkeeper positioning effect and penalty kick strategy - Noël, B.; van der Kamp, J.; Memmert, D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The position of the goalkeeper relative to the centre of the goal plays an important role in a penalty kicker`s decision where to kick the ball. Strikingly, that is also the case if penalty takers perceive the goalkeeper to be in the centre of the goal, pointing to an influence of non-conscious perception on decision-making (Masters et al., 2007). Furthermore, penalty takers can employ either a keeper dependent (KD) or a keeper independent (KI) strategy (van der Kamp, 2006). It is currently not known if the goalkeeper`s position affects decision-making of penalty takers independent of the penalty kick strategy employed. Considering that non-conscious effects on decision- making are thought to be only possible if a certain stimulus is attended and that penalty kick strategy was shown to affect a penalty taker`s allocation of attention during a penalty kick (Noël & van der Kamp, 2012) it seems worthwhile to analyse if the goalkeeper positioning effect exists regardless of penalty kick strategy employed. Methods: In Experiment 1 we advised soccer players to carry out penalty kicks under the terms of certain penalty kick strategies and keepers to start their movement before or after foot-ball contact. In addition, keepers were positioned either 10 cm to the left or right of the goal`s centre. Experiment 2 was alike the first experiment besides the fact that keepers were positioned in the perceived centre of the goal. Results: Results of Experiment 1 and 2 showed that the goalkeeper`s position relative to the (perceived) centre of the goal does not affect penalty takers` decision-making if penalty takers employ a KD strategy and the goalkeeper moves before foot-ball contact. If the goalkeeper initiates his movement after foot-ball contact and if a penalty taker employs a KI strategy (regardless of the keeper`s behavior) the effect of the goalkeeper`s position exists. Discussion: The results of both experiments expand current research on penalty kicks in soccer (Memmert et al., 2013) by showing that the effect of position of the goalkeeper is dependent on the goalkeeper`s and penalty taker`s behavior.